Report of the Working Group on Assessment of Pandalus Stocks ... - ICES (ICES Expert Group reports (until 2018), 2023)
The working Group on the Assessment of PandaIus Stocks (Chairman: Mr B. Sjostrand) met at ICES Headquarters from 10-13 February 1987 (C.Res.1986/2:5:2) to:a) assess the status of the stocks of Pandalus borealis in the North Sea, skagerrak, and Kattegat;b) update data on by-catch in the Pandalus fisheries in the areas by species and countries. ...